Reasons For Non-Compliance and Profile of Tuberculosis Patients in Urban Area of Indore - Tiwari, Sonia; Wavare, R R (National Journal of Community Medicine, 2015)
Background: India has nearly 30% of global tuberculosis burden with 280,000 deaths due to TB each year. Objective of the present study was to see the reasons for non-compliance and profile of tuberculosis patients in urban area of Indore. Methods: Four Tuberculosis Units from the Indore urban area were included in the study. 150 patients were enrolled in the study. The profile and reasons for non-compliance of the patients was recorded using semi-structured questionnaire. Results: There were 39.33% patients between 25-44 years and 51.33% patients were above 45 years. Ratio of males to females was (0.97:1). Reasons for missed doses 26.66% work related travel, 15% DOTS timing coinciding with working hours, 18.33% forgot to come, 8.33% illness or death in their family, 18.75% out of station, 12.5% onset of agricultural season. Conclusions: Reasons for non-compliance are preventable. The DOTS provider must re-enforce implications of irregular or incomplete treatment at every appropriate encounter with patient.